Assessment of the Chemical Composition and in vitro Antioxidant Activity of Mentha rotundifolia (L.) Huds Essential Oil from Algeria. Issue 5 (3rd July 2016) - Fatiha, Brahmi; Khodir, Madani; Nabila, Djerrada; Sabrina, Idir; Fatma, Harfi; Mohmed, Chibane; Moussa, Brada
Abstract: This study is designed to examine the chemical composition and antioxidant activity of Algerian Mentha rotundifolia (L.) Huds essential oil . GC and GC-MS analyses have resulted in the detection of 38 components. The piperitenone oxide (58.7 %) was a major component followed by piperitone oxide (15.9 %), terpinen-4-ol (6.3 %) and pulegone (3.9 %). The antioxidant activities of the essential oil were determined by four different test systems. DPPH, ABTS, reducing power and phosphomolybdenum assays, and showed IC 50s values of 2222.2±25.2, 133.8±4.8, 166.6±1.8, 45.2±1.2 μg/ml, respectively. These various antioxidant activities were compared to BHA, BHT, α-tocopherol and ascorbic acid as reference antioxidant compounds. The study concludes that M. rotundifolia leaves contain monoterpenoid rich oil exhibiting antioxidant activity. This may lead to extraction and production of active compounds in single or combined forms with useful applications.